2021
DOI: 10.3389/fcvm.2021.669975
|View full text |Cite
|
Sign up to set email alerts
|

Extracellular Superoxide Dismutase (EC-SOD) Regulates Gene Methylation and Cardiac Fibrosis During Chronic Hypoxic Stress

Abstract: Chronic hypoxic stress induces epigenetic modifications mainly DNA methylation in cardiac fibroblasts, inactivating tumor suppressor genes (RASSF1A) and activating kinases (ERK1/2) leading to fibroblast proliferation and cardiac fibrosis. The Ras/ERK signaling pathway is an intracellular signal transduction critically involved in fibroblast proliferation. RASSF1A functions through its effect on downstream ERK1/2. The antioxidant enzyme, extracellular superoxide dismutase (EC-SOD), decreases oxidative stress fr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 46 publications
1
8
0
Order By: Relevance
“…On the one hand, high expression of EC-SOD inhibited the increase in methylase activity and downregulated the expression of recombinant DNA methyltransferase 1(DNMT1) and DNMT-3b, thereby inhibiting the increase in HIF1α and biological oxidants. Another benefit of antioxidants was the chelation of hydrogen peroxide, which significantly reduced the activation of ERK1/2, both of which could counteract the oxidative stress associated with the pathogenesis of these cardiovascular diseases [ 62 ]. In addition, SOD3-deficient rats developed severe renal failure, arterial hypertension, and left ventricular hypertrophy at 21 weeks of age [ 62 ].…”
Section: The Application and Research Status Of Sods In Medicine Food...mentioning
confidence: 99%
“…On the one hand, high expression of EC-SOD inhibited the increase in methylase activity and downregulated the expression of recombinant DNA methyltransferase 1(DNMT1) and DNMT-3b, thereby inhibiting the increase in HIF1α and biological oxidants. Another benefit of antioxidants was the chelation of hydrogen peroxide, which significantly reduced the activation of ERK1/2, both of which could counteract the oxidative stress associated with the pathogenesis of these cardiovascular diseases [ 62 ]. In addition, SOD3-deficient rats developed severe renal failure, arterial hypertension, and left ventricular hypertrophy at 21 weeks of age [ 62 ].…”
Section: The Application and Research Status Of Sods In Medicine Food...mentioning
confidence: 99%
“…Even though the link between AMPK and cardiac fibrosis has already been suggested since the activation of AMPK can suppress fibrosis induced by various stresses (for review see [16]), regulation of the fibrotic response by AMPKα2 is still poorly understood, on the contrary to the role of AMPKα1, the major AMPK isoform in cardiac fibroblasts, which has clearly been demonstrated to control the proliferation of cardiac fibroblasts and the development of fibrosis especially through the TGF-β1/p38 axis [15]. From another side, it cannot be excluded that fibrosis observed in males was linked to mitochondrial dysfunction since it has recently been shown that oxidative stress plays a key role in myocardial fibrosis development [46,47] and excessive ROS production is a well-known feature of altered mitochondria. Nevertheless, cardiac fibrosis in OVX group was not associated with clear alteration of electron transfer chain, rather suggesting that cardiac fibrosis was an earlier event than important mitochondrial perturbations in these mice and giving weight to the hypothesis of a link between AMPK and fibrosis.…”
Section: Discussionmentioning
confidence: 99%
“…Chronic hypoxia induces oxidative stress. Recently, the administration of the antioxidant enzyme extracellular superoxide dismutase (EC-SOD) has been shown to alleviate the hypoxia-induced DNA methylation of the Ras association domain family 1 isoform A (RASSF1A) through the Ras/ERK pathway [ 116 ].…”
Section: Dna Methylation In Fibrosismentioning
confidence: 99%